The clinicopathological characteristics, oncologic outcomes and costs of “HER2-low” early breast cancer compared to HER2-zero and HER2-positive: a single-centre retrospective analysis - Rodrigues, Patrícia Rafaela; Lopes-Conceição, Luísa; Sousa, Virgínia; Coutada, Andreia; Bento, Maria José; Coimbra, Nuno; Leal, Conceição; Pereira, Deolinda; Magalhães Ferreira, Ana (Frontiers in Oncology, 2025)
BackgroundBreast cancer is a heterogeneous disease commonly classified based on hormone receptor (HR) status and human epidermal growth factor receptor 2 (HER2) expression. Recently, an intermediate category termed “HER2-low” has drawn attention for its potential prognostic and therapeutic implications. This study aimed to characterize the clinicopathological features, oncologic outcomes, and costs of “HER2-low” early breast cancer (eBC) in comparison with HER2-zero (HER2-0) and HER2-positive eBC.MethodsA single-center, retrospective analysis included patients with stage I–IIIA eBC diagnosed from January 2019 to December 2020. Patients were categorized into HER2-0, “HER2-low” (IHC 1+ or IHC 2+/ISH-negative), or HER2-positive (IHC 3+ or IHC 2+/ISH-positive). Clinicopathological data, direct medical costs, disease-free survival (DFS), and overall survival (OS) were examined. Kaplan-Meier analyses compared survival outcomes among groups, and Chi-square tests assessed differences in clinical characteristics.ResultsAmong 1,138 patients, 35.1% were HER2-0, 45.3% were “HER2-low”, and 19.5% were HER2-positive. “HER2-low” eBC showed higher rates of HR positivity compared with HER2-0 (94% vs. 89%, p=0.018) and more frequent nodal involvement (39% vs. 30%, p=0.014). Compared with HER2-positive disease, “HER2-low” tumors presented at earlier stages, had fewer grade 3 tumors, and were less frequently treated with chemotherapy (56% vs. 83%, p<0.001). No significant differences were observed in DFS or OS among the three groups within the study’s follow-up period. Costs were highest for patients with HER2-positive eBC, primarily driven by targeted therapies (trastuzumab, pertuzumab, T-DM1).ConclusionsWhile “HER2-low” eBC demonstrates distinct clinicopathological features—particularly in terms of HR positivity and histological grade—this intermediate phenotype did not exhibit worse oncologic outcomes compared with HER2–0 or HER2-positive disease in the observed timeframe. Further research is needed to validate these findings and clarify the prognostic and therapeutic significance of “HER2-low” eBC, especially as new HER2-targeting agents emerge.